Electron spin resonance from NV centers in diamonds levitating in an ion trap - T Delord; L Nicolas; L Schwab; G Hétet (New Journal of Physics, 2017)
We report observations of the electron spin resonance (ESR) of nitrogen vacancy centers in diamonds that are levitating in an ion trap. Using a needle Paul trap operating under ambient conditions, we demonstrate efficient microwave driving of the electronic spin and show that the spin properties of deposited diamond particles measured by the ESR are retained in the Paul trap. We also exploit the ESR signal to show angle stability of single trapped mono-crystals, a necessary step towards spin-controlled levitating macroscopic objects.